Cross-sectional study on N,N-dimethylformamide (DMF); effects on liver and alcohol intolerance - Kilo, Sonja; Göen, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
There are still concerns regarding occupational exposure to hepatotoxic DMF. This study was designed to evaluate possible liver damaging effects of DMF under current workplace conditions in synthetic fibres industries.Among other laboratory parameters, liver function parameters (alkaline phosphatase (ALP), aspartate aminotransferase, alanine aminotransferase and gamma-glutamyltransferase), the mean corpuscular erythrocyte volume (MCV) and carbohydrate-deficient transferrin (CDT) of the workforce of two companies present at the days of study were investigated. Internal exposure to DMF was assessed via three different biomarkers [sum of N-methylformamide and N-hydroxymethyl-N-methylformamide, N-acetyl-S-(N-carbamoyl)cysteine (AMCC) and 3-methyl-5-isopropylhydantoin (MIH)]. Alcohol consumption was assessed by means of direct ethanol metabolites (ethylglucuronide and ethylsulfate).None of the tested liver enzyme activities showed a positive association with any of the three exposure markers, nor did CDT and MCV. CDT was negatively associated with AMCC and the ALP activity negatively with all three exposure markers. Changes in liver function are seen mainly in conjunction with ethanol consumption but also with increasing body weight and age. MCV was associated with smoking. Almost half of the workers stated to experience alcohol flush reaction.The present study indicates that long-term exposure to DMF, which was specified by median urinary AMCC levels of 4.84 mg/g creatinine and DMF haemoglobin adduct levels of 60.5 nmol/MIH/g globin, respectively, does not result in any adverse liver effects. In contrast, these DMF exposure levels still elicit certain alcohol intolerance reactions.
EVALuna2:9751